2004
DOI: 10.1111/j.1471-4159.2004.02731.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene knockout of amyloid precursor protein and amyloid precursor‐like protein‐2 increases cellular copper levels in primary mouse cortical neurons and embryonic fibroblasts

Abstract: Alzheimer's disease is characterised by the accumulation of amyloid-b peptide, which is cleaved from the copper-binding amyloid-b precursor protein. Recent in vivo and in vitro studies have illustrated the importance of copper in Alzheimer's disease neuropathogenesis and suggested a role for amyloid-b precursor protein and amyloid-b in copper homeostasis. Amyloid-b precursor protein is a member of a multigene family, including amyloid precursor-like proteins-1 and -2. The copper-binding domain is similar among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 30 publications
5
72
2
Order By: Relevance
“…Increasing evidence indicates that Aβ and APP may constitutively handle copper and export it from the cell (55)(56)(57)(58)(59). Aβ is redox silent when bound to Cu 2+ as a lipid-embedded complex, and oxidation of this complex may lead to abnormal lipid integration and the release of redox activity (12,60).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that Aβ and APP may constitutively handle copper and export it from the cell (55)(56)(57)(58)(59). Aβ is redox silent when bound to Cu 2+ as a lipid-embedded complex, and oxidation of this complex may lead to abnormal lipid integration and the release of redox activity (12,60).…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal fragment Ab(1-28) has, however, been shown to undergo increased fibril formation upon interaction with zinc [25]. Another N-terminal fragment of Ab, Ab (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), forms stable oligomers in the presence of both copper and zinc [26].…”
mentioning
confidence: 99%
“…In addition, APP is thought to modulate copper homeostasis by participating in copper efflux (32). Studies in both animal and cellular models demonstrated increased levels of copper when the APP gene was knocked out (35,36). Because APP is a copper-binding protein, these effects are likely to be related to the ability of APP to bind copper; however, this link has not yet been elucidated.…”
mentioning
confidence: 99%